Skimmed Bovine Milk-Derived Extracellular Vesicles Isolated via “Salting-Out”: Characterizations and Potential Functions as Nanocarriers - Tan, Xiao-Hui; Fang, Dong; Xu, Yong-De; Nan, Tie-Gui; Song, Wen-Peng; Gu, Yang-Yang; Gu, Sheng-Ji; Yuan, Yi-Ming; Xin, Zhong-Cheng; Zhou, Li-Qun; Guan, Rui-Li; Li, Xue-Song (Frontiers in Nutrition, 2021)
Bovine milk-derived extracellular vesicles (BM-EVs) are recognized as promising nanoscale delivery vectors owing to their large availability. However, few isolation methods can achieve high purity and yield simultaneously. Therefore, we developed a novel and cost-effective procedure to separate BM-EVs via “salting-out”. First, BM-EVs were isolated from skimmed milk using ammonium sulfate. The majority of BM-EVs were precipitated between 30% and 40% saturation and 34% had a relatively augmented purity. The separated BM-EVs showed a spherical shape with a diameter of 60-150 nm and expressed the marker proteins CD63, TSG101, and Hsp70. The purity and yield were comparable to the BM-EVs isolated via ultracentrifugation while ExoQuick failed to separate a relatively pure fraction of BM-EVs. The uptake of BM-EVs into endothelial cells was dose- and time-dependent without significant cytotoxicity. The levels of endothelial nitric oxide syntheses were regulated by BM-EVs loaded with icariside Ⅱ and miRNA-155-5p, suggesting their functions as delivery vehicles. These findings have demonstrated that it is an efficient procedure to isolate BM-EVs via “salting-out”, holding great promise towards therapeutic applications.